Pelatihan Penanaman Nilai Nasionalisme dan Bela Negara di SMP Negeri 8 Denpasar: Pengabdian - Santika, I Gusti Ngurah; Ni Putu Ika Putri Sujianti; Adrianus Ahas; Limas Dwi Lestari; Yohanes Nagel; Melkianus Hona Mone (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The advancement of technology and globalization has significantly impacted the mindset of the younger generation, including the potential erosion of national values. In addressing this challenge, education plays a crucial role in instilling nationalism and the spirit of defending the nation from an early age. This community service activity aims to strengthen the national character of students through an interactive and contextual training program. The training was conducted at SMP Negeri 8 Denpasar using methods such as interactive lectures, group discussions, simulations, and reflection sessions. The outcomes were assessed through direct observation of student participation throughout the activity. The observations indicated high enthusiasm among students, who were able to understand nationalism in a broader sense and relate it to daily behaviors such as discipline, tolerance, and social responsibility. Student reflections also demonstrated personal commitments to applying the values of national defense within school and home environments. This training received positive responses from the school and was considered relevant to efforts in strengthening character education. In conclusion, a participatory and practical training approach is effective in instilling national values in junior high school students. This activity is expected to serve as a replicable model in other schools as part of efforts to reinforce the nation’s identity..